The Role of Student Affairs in a New University in a Conflict Zone - Sengupta, Enakshi (Journal of International Students, 2017)
Higher education necessitates an understanding that students cannot be confined to the classroom, as a large part of their curriculum comprises extracurricular activities to educate  intellectually, in spirit, and body. AS a result, community building, advising, and career development became a part of the traditional routine of student affairs. This article explores the role of student affairs in a newly formed university in a conflict zone ravaged by war and terrorism for decades. The data explored in this article reveals some interesting facts, which are different from that of the traditional student affairs manager. In this university, student affairs personnel are viewed as a ‘job giver,’ someone who will arrange funds, bursaries, and scholarships in keeping with the war-ravaged economic scenario of the province in northern Iraq.